Effect of Nitrogen Fertilization on the Growth and Seed Yield of Sesame (Sesamum indicum L.) - Gebregergis Zenawi; Amare Mizan (International Journal of Agronomy)
Sesame (Sesamum indicum L.) is grown mainly in the tropics. It is typically grown by smallholders with nearly all of its production in developing countries. It is an important source of high-quality oil and protein. Inappropriate use of fertilizers and monocropping are among the major production constraints. The objective of this paper is therefore to review the effect of N fertilizers on sesame growth and productivity. Growth and yield of sesame are greatly influenced by the application of N fertilizer. In most of the sesame-producing countries, optimum seed yield of sesame was obtained from application of 46–100 kg·N/ha. Adequate nitrogen fertilization also improves uptakes of other nutrients, particularly P and K and some micronutrients. Preemergence application of mobile nitrogen (urea) is less efficient due to losses. Mobile form of N fertilizer became available within two days for the crop. Split N applications where the N fertilizer is applied at different growth stages of the crop increases productivity. Side-dress application is one of the easiest ways to maximize nitrogen use efficiency. N fertilizers should be placed 3–5 cm deeper than the seeds and 5–10 cm apart from the plant for side dress but not far than 20 cm. Under optimal environmental conditions, nitrogen fertilizer has no effect on phonological traits but on the growth parameters. In the potential areas, application of 46–100 kg·N/ha gives maximum yield and lowering the application of N to less than 46 kg·N/ha in marginal areas is economical.